Dual-language narrative intervention outcomes for a bilingual adolescent with down syndrome. Issue 4 (2nd October 2021) - Gorman, Brenda K.; Martinez, Guadalupe; Pina Garcia, Lindsay
ABSTRACT: The goal of this investigation was to address gaps in the literature regarding dual-language learning in children with Down syndrome (DS). The investigators examined the outcomes of a dual-language narrative intervention and cross-language transfer in a bilingual (Spanish-English) adolescent with DS. Results revealed moderate to large effects in narrative macrostructural skills, with bi-directional cross-language transfer, and no secondary change in microstructural skills. With gains in both languages, findings indicated that the participant benefitted from the dual-language condition, thereby contributing to the emerging evidence base needed to support professionals and families as they engage in instructional decision-making for children with DS.